2010
DOI: 10.1073/pnas.0912319107
|View full text |Cite
|
Sign up to set email alerts
|

Inverted-U-shaped correlation between dopamine receptor availability in striatum and sensation seeking

Abstract: Sensation seeking is a core personality trait that declines with age in both men and women, as do also both density and availability of the dopamine D 2/3 receptors in striatum and cortical regions. In contrast, novelty seeking at a given age relates inversely to dopamine receptor availability. The simplest explanation of these findings is an inverted-U-shaped correlation between ratings of sensation seeking on the Zuckerman scale and dopamine D 2/3 receptor avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
108
3
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(124 citation statements)
references
References 37 publications
7
108
3
6
Order By: Relevance
“…Animal studies have demonstrated that testosterone significantly influences dopamine neural transmission in the adolescent brain (Allen et al, 2015). Furthermore, dopamine receptor density has been shown to correlate with motivational forms of impulsive behaviour (sensation seeking) in adult men (Gjedde et al, 2010). In addition, Braams and colleagues (2015) have shown that pubertal testosterone is associated with an increased response to rewards in the striatum.…”
Section: Introductionmentioning
confidence: 98%
“…Animal studies have demonstrated that testosterone significantly influences dopamine neural transmission in the adolescent brain (Allen et al, 2015). Furthermore, dopamine receptor density has been shown to correlate with motivational forms of impulsive behaviour (sensation seeking) in adult men (Gjedde et al, 2010). In addition, Braams and colleagues (2015) have shown that pubertal testosterone is associated with an increased response to rewards in the striatum.…”
Section: Introductionmentioning
confidence: 98%
“…In this study, the authors suggest that the given dose may have been too high for those with higher DA D 2 levels, and that a smaller dose may have had a more pleasant effect, suggesting that drug abusers in general suffer from lower DA gains in the striatum (17,19,25).…”
Section: Addiction and Dopaminementioning
confidence: 93%
“…Drug abusers in general have low DA D 2 receptor levels in striatum and a low DA release (17), which is linked to the observation that repeated intake of addictive substances such as amphetamine or cocaine significantly downregulates available DA D 2 receptor levels, understandable as a compensation for the high and persistent DA concentration in the synaptic cleft (18). Gjedde et al (19) showed that healthy Danish men who are more sensation-seeking than other healthy men have significantly fewer available DA receptors in striatum because a greater fraction are occupied by the increased extracellular DA. This greater dopamine in turn is thought to be the result of constant dopaminergic stimulation, yielding the lower binding potential (BP) of the receptors.…”
Section: Addiction and Dopaminementioning
confidence: 99%
“…We calculated BP ND as the ratio of the volume V T in ROIs with specifically displaceable binding and the volume V ND of distribution in a chosen reference region with specifically nondisplaceable binding, here selected as the volume determined for the corpus callosum (BP ND 5 0) (22).…”
Section: Kinetic Analysis Of 11 C-yohimbine Uptake and Distributionmentioning
confidence: 99%